A construção cotidiana da atenção primária à saúde com enfoque intercultural em uma região da Amazônia colombiana: vivências de indígenas e profissionais de saúde - Saidy Eliana Arias Murcia (2020)
In 2016, the implementation of a new health model began in Colombia. The state of Guainía, located in the northeast of the Amazon, was chosen to start implementation as a pilot for territories with a dispersed population in the country, with the primary strategic objective of primary health care (PHC) with an intercultural approach. The way in which the experience of implementing the new imposed guidelines was happening, specifically in the day-to-day life of the social actors involved in PHC, motivated the development of this research. The objective was understand the process of daily construction of PHC from the perspective of indigenous and health professionals, in Guainía, Colombia. It is a unique holistic case study with a qualitative approach, based on Comprehensive Sociology of Everyday Life. The study scenarios were the state hospital, centers and health posts, belonging to the public health care network. The participants were: 22 indigenous users, 26 health professionals and three key participants (a traditional doctor, an indigenous leader and an administrative advisor), intentionally selected and whose participation was voluntary. The field research was carried out between the months of February to June 2018. For the collection and production of data, guided interviews were conducted through a semi-structured script and direct observation. The data analysis was outlined by Bardin's thematic content analysis technique (2011), following three chronological poles: The emerging results were organized into two broad empirical categories: 1) Primary health care in Guainía: the history of what was and what is being built; 2) Interculturality in the routine of primary health care in Guainía; each composed of four subcategories. The analysis of the data showed that the PHC construction process in Guainía runs through the set of actions developed in the daily work of professionals with indigenous users, which have been delineated by constructions and learning prior to the new health model. However, there was a persistence of the disease-centered care model and based on the curative logic that guides the organization of PHC services in the region, both in rural and urban contexts. The data show that, in this dynamic, interculturality appears as a permanent process of negotiations and articulations present in the daily lives of indigenous people and health professionals. It materializes the encounter and exchange of heterogeneous ways of thinking-knowing, which allow new interpretations of knowledge and health practices, despite the fact that this process is permeated by conflicts, asymmetries and contradictions. The aim of this study is to generate contributions that make it possible to strengthen the implementation of the care model in the Guainía region, as well as in other regions of Colombia with similar characteristics. The aim is also to contribute to the development of proposals and public policies that address the local and regional health needs in remote areas, which are difficult to access and inhabited by indigenous and multicultural populations.